Non-gas-production type lithium-rich lithium ferrite positive electrode lithium supplementing material and preparation method and application of non-gas-production type lithium-rich lithium ferrite positive electrode lithium supplementing material

By ball milling and heating with sulfur or phosphorus element and conductive agents, non-gas-producing composite materials are formed, the problem of lithium lithium ferrate producing oxygen during charging is solved, the safety and cycle stability of the battery are improved, and the prerequisite for large-scale application is realized.

CN119786607AActive Publication Date: 2025-04-08TONGJI UNIV

Patent Information

Application Number
CN202411977956.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

As a positive electrode lithium lithium supplement agent, lithium lithium-rich ferrate produces oxygen during charging, causing potential dangers to the battery and limiting its large-scale application.

Method used

By ball milling the lithium-rich lithium ferrate with sulfur or phosphorus element and conductive agent, and heating it at high temperature, sulfur or phosphorus is adsorbed on Kochen Black and coated on the surface of lithium-rich lithium ferrate to form a non-gas-producing composite material.

Benefits of technology

It effectively inhibits the oxygen production of lithium-rich lithium ferrate during charging, improves the safety and circulation stability of lithium-ion batteries, and realizes the prerequisite for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786607A_ABST
    Figure CN119786607A_ABST
Patent Text Reader

Abstract

The invention relates to a non-gas-production type lithium-rich lithium ferrite positive electrode lithium supplement material and a preparation method and application thereof.The preparation method comprises the steps that common lithium-rich lithium ferrite is used as a raw material, the lithium-rich lithium ferrite, elemental sulfur or phosphorus and a conductive agent are subjected to ball milling and then heated at the high temperature, the elemental sulfur or phosphorus and the conductive agent are mixed to be uniform, the surface of the lithium-rich lithium ferrite is coated with the mixture, and the surface of the lithium-rich lithium ferrite is coated with the conductive agent to obtain the non-gas-production type lithium-rich lithium ferrite positive electrode lithium supplement material; and finally obtaining the composite material. Compared with the prior art, the lithium supplementing material disclosed by the invention is added into positive electrode slurry, so that the purpose of positive electrode pre-lithiation can be achieved, and the problem of oxygen release of a lithium-rich lithium ferrite lithium supplementing agent in a charging process can be inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium replenishment of lithium ion batteries, and relates to a non-gas-generating lithium-rich lithium ferrite positive electrode lithium replenishment material and a preparation method and application thereof. Background Art

[0002] With the continuous progress and development of the new energy industry, the important field of lithium-ion batteries has also received extensive attention. As one of the main research hotspots, pre-lithiation technology is a very promising technical direction in lithium-ion batteries.

[0003] During the charging and discharging process, lithium-ion batteries will inevitably consume limited lithium ions due to the formation of SEI, resulting in irreversible lithium loss, which poses certain challenges and risks to the battery's cycle life and coulombic efficiency. To address this problem, lithium replenishment technology is a very effective solution.

[0004] Currently, the most popular lithium replenishment technologies are positive electrode replenishment and negative electrode replenishment. Negative electrode replenishment has made some progress, but since negative electrode replenishment involves the use of metallic lithium, and metallic lithium easily reacts with water in the air, it has high environmental requirements, which poses a great challenge to the large-scale application of negative electrode replenishment. Relatively speaking, positive electrode replenishment is a simple and effective implementation method, which only requires adding an appropriate amount of lithium replenisher during the positive electrode homogenization process.

[0005] As a positive electrode lithium supplement, lithium iron oxide has great application prospects. Its theoretical specific capacity can reach 690mAh / g, which is much higher than the currently widely used lithium nickel oxide lithium supplement. However, lithium iron oxide also has a problem that cannot be ignored, that is, during the charging process, oxygen will inevitably be produced, which will cause potential danger to the battery. This is also the main reason why lithium iron oxide is difficult to be applied on a large scale. Summary of the invention

[0006] The purpose of the present invention is to provide a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material and its preparation method and application, so as to solve the problems that the currently commonly used lithium supplement agent lithium-rich lithium ferrite produces gas and is difficult to use on a large scale.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a non-gas-generating lithium-rich lithium iron oxide positive electrode lithium supplement material, comprising the following steps:

[0009] (1) taking lithium iron-rich lithium (Li5FeO4), sulfur or phosphorus, and a conductive agent and grinding them so that the three are evenly mixed to obtain a mixture;

[0010] (2) The mixture is ball-milled and then heated and kept warm, so that sulfur or phosphorus is adsorbed on the Ketjen black and coated on the surface of the lithium iron-rich lithium oxide to obtain the target product.

[0011] Furthermore, the grinding in step (1) is carried out in a dry atmosphere with the relative humidity maintained below 10%.

[0012] Furthermore, in step (1), the mass proportion of the conductive agent in the mixture is 2 to 10%.

[0013] Furthermore, in step (1), the molar ratio of lithium-rich lithium ferrite to sulfur or phosphorus is 1:1.

[0014] Furthermore, in step (1), the conductive agent is Ketjen black, carbon black or carbon nanotubes, etc.

[0015] Furthermore, in step (2), during the ball milling process, the mass ratio of the ball milling material to the ball milling beads is 1:(8-12).

[0016] Furthermore, in step (2), the rotation speed of the ball mill is 150 to 500 rpm, preferably 150 to 250 r / min, and the time is 2 to 10 h, preferably 2 to 4 h.

[0017] Furthermore, in step (2), the ball milling and heating and heat preservation processes are both carried out under an inert atmosphere, with an oxygen concentration lower than 10 ppm and a water vapor concentration lower than 0.2 ppm.

[0018] Furthermore, in step (2), when the mixture is mixed with lithium-rich lithium ferrite, sulfur and a conductive agent, it is heated to 130-170° C. and kept warm for 1-3 hours.

[0019] Furthermore, in step (2), when the mixture is mixed with lithium-rich lithium ferrite, phosphorus element and conductive agent, it is first heated to 400-500°C, kept warm for 1-3 hours, and then kept warm at 200-300°C for 24-72 hours.

[0020] The present invention uses common lithium-rich ferrite as a raw material, and after ball-milling lithium-rich ferrite, sulfur or phosphorus and a conductive agent, heats them at a high temperature, so that the sulfur or phosphorus and Ketjen black are evenly adsorbed and coated on the surface of the lithium-rich ferrite, and finally a composite material is obtained. Ball milling not only reduces the particle size of the lithium-rich ferrite, but also makes the contact of the three more uniform. Adding the composite material to the positive electrode slurry can not only achieve the purpose of positive electrode pre-lithiation, but also suppress the problem of oxygen release of the lithium-rich ferrite lithium supplement during charging. Since lithium-rich ferrite releases lithium ions through the oxidation of oxygen anions, sulfur or phosphorus is added, and sulfur or phosphorus elements are used as oxidation active sites to replace oxygen anions to oxidize into oxygen, thereby reducing the effect of the lithium supplement gas production on the battery itself.

[0021] In addition, the present invention has found through research that if ketjen black is not used and sulfur and lithium-rich ferrite are directly ball-milled, sulfur or P will be evenly distributed around the lithium-rich ferrite after ball milling. However, due to the poor conductivity of sulfur or P, even if the final ball-milled sample is added to the positive electrode, sulfur or P will not only not react with the lithium-rich ferrite, but will also hinder the capacity of the lithium-rich ferrite to a certain extent. Therefore, ketjen black plays a key role in promoting the reaction of lithium-rich ferrite and sulfur or P due to its strong conductivity and large specific surface area.

[0022] In addition, the present invention studies the influence of ball milling conditions on the composite material. Ball milling is mainly to crush the lithium iron oxide rich in tens of microns, so that the particle size of the lithium iron oxide rich in lithium iron oxide is reduced to a few microns, and the raw materials are evenly mixed.

[0023] In a second aspect, the present invention provides a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material, which is prepared by the preparation method described above.

[0024] In a third aspect, the present invention provides an application of a non-gas-generating lithium iron oxide-rich positive electrode lithium replenishing material in lithium replenishing of lithium-ion batteries.

[0025] Compared with the prior art, the non-gas-generating lithium-rich iron oxide material provided by the present invention uses sulfur or phosphorus as the oxidation active site to replace the oxidation of oxygen, thereby suppressing the generation of oxygen while achieving the lithium supplement effect, thus solving the problem of lithium-rich iron oxide in practical applications. After oxidation, sulfur or phosphorus forms corresponding sulfate or phosphate, which will not cause negative effects on battery cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the cycle performance of the full battery in Example 1 of the present invention;

[0027] Figure 2 is the cycle performance of the full battery in Example 2 of the present invention;

[0028] Figure 3 The cycle performance of the full battery in comparison 1 of the present invention;

[0029] Figure 4 The cycle performance of the full battery in Comparative Example 2 of the present invention;

[0030] Figure 5 is the charging curve of the half-battery in Example 3 of the present invention;

[0031] Figure 6 The gas production test results of DEMS in Example 3 of the present invention are as follows;

[0032] Figure 7This is the XPS test result of Example 3 of the present invention after charging;

[0033] Figure 8 The XRD test results of Example 3 of the present invention before and after charging;

[0034] Fig. 9 The results are as follows: the filtrate obtained by soaking the electrode in Example 3 of the present invention after charging is immersed in an aqueous solution and a BaCl2 acid solution respectively;

[0035] Fig.10 is the charging curve of the half-battery in comparative example 3 of the present invention;

[0036] Fig.11 The scanning electron microscope image and energy spectrum of the lithium-rich lithium ferrite-phosphorus composite material prepared in Example 4 of the present invention;

[0037] Fig.12 This is a scanning electron microscope image of the lithium-rich lithium ferrate raw material used in Example 4 of the present invention;

[0038] Fig.13 The cycle performance of the full battery in Example 4 of the present invention and Comparative Example 4;

[0039] Fig.14 The charge-discharge curves and DEMS curves of Example 5 and Comparative Example 5;

[0040] Fig.15 Ultrasonic images of the batteries during the first cycle of the soft-pack batteries of Example 6 and Comparative Example 6. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0042] In the following embodiments, the component ratio of the lithium iron phosphate positive electrode slurry used is lithium iron phosphate: conductive carbon SuperP: binder PVDF (polyvinylidene fluoride) = 8:1:1, NMP (N-methylpyrrolidone) is used as the solvent, and the solid content is about 40%.

[0043] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.

[0044] Embodiment 1:

[0045] A sample obtained by ball milling a mixture of lithium-rich iron phosphate (Li5FeO4), sulfur and Ketjen black (wherein the molar ratio of lithium-rich iron phosphate to sulfur is 1:1 and the mass of Ketjen black accounts for 5% of the total mass of the mixture) at 150 r / min for 2 h was heated to 150 ° C for 2 h, and then 5% of lithium-rich iron phosphate (i.e., 5% of the mass of the positive electrode active material LFP, the same below) was added to the lithium iron phosphate positive electrode slurry, and the lithium iron phosphate surface capacity of 1.2 mAh / cm 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2 The graphite anode was assembled into a CR2025 button cell in an argon-protected glove box. It was first charged to 3.7V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.5V at 0.05C to complete the first cycle. Then, it was charged to 3.7V at 0.1C constant current and constant voltage, and discharged to 2.5V at 0.1C constant current and constant voltage, activated for three cycles, and then a long cycle test was performed at a rate of 0.5C, with a long cycle voltage range of [2.5V, 3.7V].

[0046] Figure 1 This is the cycle performance of the full battery in Example 1 of the present invention.

[0047] from Figure 1 It can be seen that in the first 100 cycles of the full battery cycle, there is almost no capacity decay, and the lithium-replenishing effect of lithium-rich lithium iron oxide itself is also obtained, without causing adverse effects on the battery.

[0048] Embodiment 2:

[0049] The sample obtained by hand grinding a mixture of lithium-rich iron phosphate, sulfur and ketjen black (wherein the molar ratio of lithium-rich iron phosphate to sulfur is 1:1 and the mass of ketjen black accounts for 5% of the total mass of the mixture) for 20 minutes was heated to 150°C for 2 hours, and then added to the lithium iron phosphate positive electrode slurry with a content of 5% lithium-rich iron phosphate to obtain a lithium iron phosphate surface capacity of 1.2 mAh / cm 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2 The graphite anode was assembled into a CR2025 button cell in an argon-protected glove box. It was first charged to 3.7V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.5V at 0.05C to complete the first cycle. Then, it was charged to 3.7V at 0.1C constant current and constant voltage, and discharged to 2.5V at 0.1C constant current and constant voltage, activated for three cycles, and then a long cycle test was performed at a rate of 0.5C, with a long cycle voltage range of [2.5V, 3.7V].

[0050] Figure 2 This is the cycle performance of the full battery in Example 2 of the present invention.

[0051] from Figure 2 It can be seen that in the first 300 cycles of the full battery cycle, although the capacity is affected by polarization in the first few cycles, it slowly recovers to normal specific capacity and has the capacity effect of replenishing lithium, which is almost consistent with the capacity of ordinary 5% lithium-rich lithium iron oxide in the first 300 cycles. While inhibiting gas production, it also has the effect of replenishing lithium. It can be seen that hand grinding will cause Li5FeO4 to not combine tightly with sulfur, making the battery cycle performance not as good as ball milling, but it still has a certain effect of inhibiting gas production and replenishing lithium.

[0052] Comparative Example 1:

[0053] The lithium iron oxide rich lithium was directly added to the lithium iron phosphate positive electrode slurry at a content of 5%, and the lithium iron phosphate surface capacity was obtained to be 1.2 mAh / cm 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2 The graphite anode was assembled into a CR2025 button cell in an argon-protected glove box. It was first charged to 3.7V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.5V at 0.05C to complete the first cycle. Then, it was charged to 3.7V at 0.1C constant current and constant voltage, and discharged to 2.5V at 0.1C constant current and constant voltage, activated for three cycles, and then a long cycle test was performed at a rate of 0.5C, with a long cycle voltage range of [2.5V, 3.7V].

[0054] Figure 3 The cycle performance of the full battery in comparison 1 of the present invention.

[0055] from Figure 3 It can be seen that in the first 600 cycles of the full battery cycle, although the lithium replenishment effect in the first 300 cycles was very good, the lithium-rich lithium iron oxide in the positive electrode continuously released oxygen due to charging, which had a bad effect on the cycle performance of the battery. After 300 cycles, a faster capacity decay soon occurred.

[0056] Comparative Example 2:

[0057] Prepare lithium iron phosphate positive electrode slurry and obtain a lithium iron phosphate surface capacity of 1.2 mAh / cm 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2 The graphite anode was assembled into a CR2025 button cell in an argon-protected glove box. It was first charged to 3.7V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.5V at 0.05C to complete the first cycle. Then, it was charged to 3.7V at 0.1C constant current and constant voltage, and discharged to 2.5V at 0.1C constant current and constant voltage, activated for three cycles, and then a long cycle test was performed at a rate of 0.5C, with a long cycle voltage range of [2.5V, 3.7V].

[0058] Figure 4 This is the cycle performance of the full battery in Comparative Example 2 of the present invention.

[0059] from Figure 4 It can be seen that since ordinary lithium iron phosphate full batteries do not contain lithium-rich lithium iron oxide, there is no lithium-replenishing effect. During the 600-cycle cycle, the capacity has been uniformly decayed, and there is no negative impact caused by the gas production of lithium-rich lithium iron oxide without lithium-replenishing agent.

[0060] Embodiment 3:

[0061] The sample obtained by ball milling a mixture of lithium-rich iron ore, sulfur and Ketjen black (wherein the molar ratio of lithium-rich iron ore to sulfur is 1:1 and the mass of Ketjen black accounts for 5% of the total mass) at 150 r / min for 2 h was heated to 150 ° C for 2 h, and then slurried with SP (conductive carbon Super P) and PVDF at a mass ratio of 7:2:1 to obtain an active material loading of 2.8 mg / cm 2 The positive electrode sheet was assembled with the lithium sheet negative electrode in an argon-protected glove box to form a CR2025 button cell. It was charged to 4.5V at a rate of 0.02C.

[0062] Figure 5 This is the charging curve of the half-battery in Example 3 of the present invention.

[0063] from Figure 5 It can be seen that most of the capacity of lithium iron ore rich lithium can be released during the charging process, and it will still have the effect of a lithium supplement.

[0064] Figure 6 This is the gas production test result of electrochemical differential mass spectrometry (DEMS) in Example 3 of the present invention.

[0065] from Figure 6 It can be seen that during the charging process of the treated lithium-rich lithium iron ore sample, almost no oxygen generation was observed during the DEMS test process, thus proving that the method implemented by the present invention has a certain inhibitory effect on the gas production of lithium-rich lithium iron ore.

[0066] Figure 7 This is the XPS test result of Example 3 of the present invention after charging.

[0067] from Figure 7 It can be seen that after the electrode was fully charged and subjected to XPS testing, it was found that the basic sulfur had become +6 valence, which means that the sulfur element has become sulfate. This also indirectly proves that the sulfur element has replaced the oxygen element in the lithium iron ore-rich battery to undergo an oxidation reaction, thereby inhibiting the production of oxygen to a certain extent.

[0068] Figure 8These are the XRD test results of Example 3 of the present invention before and after charging.

[0069] from Figure 8 It can be seen that before the electrode is charged, the XRD test can clearly detect the peak of lithium-rich lithium iron oxide Li5FeO4, and after charging, the peak of lithium-rich lithium iron oxide disappears, indicating that the lithium-rich lithium iron oxide is completely reacted during the charging process.

[0070] Fig. 9 The filtrate obtained by soaking the electrode in Example 3 of the present invention after charging is immersed in an aqueous solution and a BaCl2 acid solution respectively. The attached figure shows the precipitate obtained after filtration.

[0071] from Fig. 9 It can be seen that the filtrate obtained by soaking has no obvious phenomenon in water, but after being added to the acid solution of BaCl2, white turbidity quickly appeared, indicating that barium sulfate precipitate was generated. This phenomenon shows that sulfur generates sulfate ions after reacting with lithium iron-rich lithium, and the precipitate is obtained by filtration.

[0072] Comparative Example 3:

[0073] Lithium-rich ferrite was directly mixed with SP and PVDF in a ratio of 7:2:1 to prepare a slurry, and the active material loading was 2.8 mg / cm 2 The positive electrode sheet was assembled with the lithium sheet negative electrode in an argon-protected glove box to form a CR2025 button cell. It was charged to 4.5V at a rate of 0.02C.

[0074] Fig.10 This is the charging curve of the half-battery in Comparative Example 3 of the present invention.

[0075] from Fig.10 It can be seen that most of the capacity of the lithium-rich lithium iron oxide can be released during the charging process, and it still has the effect of a lithium supplement. However, since the conductivity of the lithium-rich lithium iron oxide itself is not good enough, the capacity is not as good as the mixture doped with Ketjen black in Example 3.

[0076] Embodiment 4:

[0077] The sample obtained by ball milling a mixture of lithium-rich iron phosphate, P and Ketjen black (wherein the molar ratio of lithium-rich iron phosphate to P is 1:1 and the mass of Ketjen black accounts for 5% of the total mass) at 150 r / min for 2 h was heated to 450 ° C for 2 h, then cooled to 280 ° C for 48 h, and then added to the lithium iron phosphate positive electrode slurry at a content of 3 wt%, and the lithium iron phosphate surface capacity of 1.2 mAh / cm was obtained. 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2The graphite anode was assembled into a CR2025 button cell in an argon-protected glove box. It was first charged to 3.8V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.0V at 0.05C constant current to complete the first cycle. Then, it was charged to 3.8V at 0.1C constant current, and discharged to 2.0V at 0.1C constant current for three cycles of activation. Then, a long cycle test was performed at a rate of 0.5C, and the long cycle voltage range was [2.0V, 3.8V].

[0078] Comparative Example 4:

[0079] Prepare lithium iron phosphate positive electrode slurry and obtain a lithium iron phosphate surface capacity of 1.2 mAh / cm 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2 The graphite anode was assembled into a CR2025 button cell in an argon-protected glove box. It was first charged to 3.8V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.5V at 0.05C to complete the first cycle. Then, it was charged to 3.8V at 0.1C constant current and constant voltage, and discharged to 2.0V at 0.1C constant current, activated for two cycles, and then a long cycle test was performed at a rate of 0.5C, with a long cycle voltage range of [2.0V, 3.8V].

[0080] Fig.11 The scanning electron microscope image and energy spectrum of the lithium-rich lithium ferrite phosphorus composite material prepared in Example 4 of the present invention.

[0081] Fig.12 This is a scanning electron microscope image of the lithium-rich lithium ferrate raw material used in Example 4 of the present invention.

[0082] from Fig.11 and Fig.12 By comparison, it can be seen that the particle size of the lithium-rich ferrite-phosphorus composite material is greatly reduced after ball milling, which is about 1 to 2 μm, and the lithium-rich ferrite, phosphorus and carbon are evenly distributed.

[0083] Fig.13 The cycle performance of the full battery in Example 4 of the present invention and Comparative Example 4.

[0084] from Fig.13 It can be seen that in the first 1000 cycles of the full battery cycle, the full battery in Example 4 exhibits good lithium replenishment performance and cycle stability compared to the full battery in Comparative Example 4, and improves the coulombic efficiency during the cycle.

[0085] Embodiment 5:

[0086] The mixture of lithium-rich iron ore, P and Ketjen black (wherein the molar ratio of lithium-rich iron ore to P is 1:1, and the mass of Ketjen black accounts for 5% of the total mass) was milled at 150 r / min for 2 h, heated to 450 ° C for 2 h, then cooled to 280 ° C for 48 h, and then slurried with SP and PVDF in a ratio of 7:2:1 to obtain an active material loading of 3.6 mg / cm 2 The positive electrode sheet was assembled with the lithium sheet negative electrode in an argon-protected glove box to form a CR2025 button cell. It was charged to 4.5V at a rate of 0.02C.

[0087] Comparative Example 5:

[0088] Lithium-rich ferrite was directly mixed with SP and PVDF in a ratio of 7:2:1 to prepare a slurry, and the active material loading was 3.6 mg / cm 2 The positive electrode sheet was assembled with the lithium sheet negative electrode in an argon-protected glove box to form a CR2025 button cell. It was charged to 4.5V at a rate of 0.02C.

[0089] Fig.14 The charge-discharge curves and DEMS curves of Example 5 and Comparative Example 5 are shown.

[0090] from Fig.14 It can be seen that the gas production of the lithium-rich lithium iron phosphate composite material during the decomposition process is significantly suppressed, which is greatly reduced compared with the lithium-rich lithium iron phosphate.

[0091] Embodiment 6:

[0092] The sample obtained by ball milling a mixture of lithium-rich iron phosphate, P and Ketjen black (wherein the molar ratio of lithium-rich iron phosphate to P is 1:1 and the mass of Ketjen black accounts for 5% of the total mass) at 150 r / min for 2 h was heated to 450 ° C for 2 h, then cooled to 280 ° C for 48 h, and then added to the lithium iron phosphate positive electrode slurry at a content of 3%, and the lithium iron phosphate surface capacity of 1.2 mAh / cm was obtained. 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2 The graphite negative electrode is assembled into a soft pack battery in a dry room. First, it is charged to 3.8V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.0V at 0.05C constant current to complete the first cycle.

[0093] Comparative Example 6:

[0094] The lithium iron oxide was added to the lithium iron phosphate positive electrode slurry at a content of 3%, and the lithium iron phosphate surface capacity was obtained to be 1.2 mAh / cm 2 The positive electrode has a surface capacity of 1.45 mAh / cm 2The graphite negative electrode is assembled into a soft pack battery in a dry room. First, it is charged to 3.8V at 0.1C, then charged to 4.3V at 0.01C, and then discharged to 2.0V at 0.05C constant current to complete the first cycle.

[0095] Fig.15 Ultrasonic images of the batteries during the first cycle of the soft-pack batteries of Example 6 and Comparative Example 6.

[0096] from Fig.15 It can be seen that the gas production area (blue area) of the soft-pack battery with added lithium iron oxide-rich phosphorus composite material during the first cycle is significantly reduced, and a large amount of gas production occurs during the first cycle of the soft-pack battery with added lithium iron oxide-rich phosphorus composite material, indicating the large-scale application prospects of lithium iron oxide-rich phosphorus composite materials.

[0097] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a non-gas-generating lithium-rich lithium iron oxide positive electrode lithium supplement material, characterized in that: The following steps are involved: (1) grinding lithium iron-rich lithium, sulfur or phosphorus, and a conductive agent to uniformly mix the three to obtain a mixture; (2) The mixture is ball-milled and then heated and kept warm, so that sulfur or phosphorus is adsorbed on the Ketjen black and coated on the surface of the lithium iron-rich lithium oxide to obtain the target product.

2. The method for preparing a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material according to claim 1, characterized in that: The grinding in step (1) is carried out in a dry atmosphere with the relative humidity maintained below 10%.

3. The method for preparing a non-gas-generating lithium-rich lithium iron oxide positive electrode lithium supplement material according to claim 1, characterized in that: In step (1), the mass proportion of the conductive agent in the mixture is 2 to 10%.

4. The method for preparing a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material according to claim 1, characterized in that: In step (1), the molar ratio of lithium-rich lithium ferrite to sulfur or phosphorus is 1:

1.

5. The method for preparing a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material according to claim 1, characterized in that: In step (1), the conductive agent is Ketjen black, carbon black or carbon nanotubes.

6. The method for preparing a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material according to claim 1, characterized in that: In step (2), during the ball milling process, the mass ratio of the ball milling material to the ball milling beads is 1:(8-12); The ball milling speed is 150-500 rpm and the time is 2-10 hours.

7. The method for preparing a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material according to claim 1, characterized in that: In step (2), the ball milling and heating and heat preservation processes are carried out under an inert atmosphere, with an oxygen concentration lower than 10 ppm and a water vapor concentration lower than 0.2 ppm.

8. The method for preparing a non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material according to claim 1, characterized in that: In step (2), when the mixture is mixed with lithium-rich lithium ferrite, sulfur and a conductive agent, it is first heated to 130-170° C. and kept warm for 1-3 hours; When the mixture is mixed with lithium-rich lithium ferrite, phosphorus and a conductive agent, it is first heated to 400-500° C., kept warm for 1-3 hours, and then kept warm at 200-300° C. for 24-72 hours.

9. A non-gas-generating lithium-rich lithium ferrite positive electrode lithium supplement material, prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the non-gas-generating lithium-rich lithium ferrite positive electrode lithium replenishing material as claimed in claim 9 in lithium replenishing of lithium-ion batteries.

Citation Information

Patent Citations

  • Modified positive electrode lithium supplement additive and preparation method and application thereof

    CN115832471A

  • Lithium supplement material for positive electrode of lithium ion battery, positive electrode plate of lithium ion battery and lithium ion battery

    CN116565171A

  • Lithium-rich lithium ferrite positive electrode lithium supplementing material and preparation method and application thereof

    CN117154095A

  • Lithium-boron-carbon-coated lithium-rich lithium ferrite positive electrode lithium supplementing material as well as preparation method and application thereof

    CN117239083A

  • Lithium-rich lithium ferrite material as well as preparation method and application thereof

    CN118970048A

Cited By

  • Low-gas-production type positive electrode lithium supplementing material as well as preparation method and application thereof

    CN122202573A